Meta-analysis of The Ethopedagogical Based Blended Learning Model on Students' Problem Solving Ability - Loso Judijanto; Andrie Oktavio; Jeheskial Saudale; Rian Mitasari; Sutarto Sutarto; Miftachul Amri; Tomi Apra Santosa (Universitas Muhammadiyah Enrekang, 2024)
The 21st century has had such a big influence on the development of the world of education. Education today has been based on technology which is very helpful for teachers in carrying out learning activities. Blended learning is a learning model that utilizes technology. However, the many applications of the blended learning model have not reached in-depth conclusions related to ethnopedagogy-based blended learning models on students' problem-solving abilities. This study aims to determine the effect of ethnopedagogy-based blended learning models on students' problem-solving skills. This study is a type of meta-analysis research. The research data comes from an analysis of 17 national and international journals that have been published in 2019-2024. The criteria for data eligibility are that research must be experimental methods or quasi-experiments; Research comes from national and international journals indexed by SINTA and Scopus, Research related to ethnopedagogy-based blended learning models on students' problem-solving abilities, research data obtained through trusted databases namely mendeley, ERIC, ScienceDirect, Wiley and Google Scholar. The technique of displaying data samples is purposive sampling. Data analysis in research is quantitative data analysis by calculating the value of effect size with the help of the OpenMEE application. The results showed that the application of ethnopedagogy-based blended learning models had a significant effect on students' problem-solving abilities with an average effect size value of 0.927 with a high effect size category.